Islamic Education and Early Islamization in Java - Muhammad Jukhairin (Edumaspul: Jurnal Pendidikan, 2023)
The introduction of Islam to Jawa was connected to the growth of Islamic education during the pre-Islamic era. Metal dealers who interacted with the local populace helped Islamize the archipelago by spreading the religion across Jawa. Early Islamic teaching occurred wherever and whenever there was interaction between muballiq merchants and the local populace, as opposed to being restricted to a certain time or location. The surau, mosque, manor mansions, and affluent dwellings come first in the schooling system before the environment.